(untitled) (Conferencea, 2022)
The field of computer technology has grown significantly. As a result, this technology is now used in many facets of our existence. The development of additional amenities has been facilitated by the internet, which has enhanced the communication infrastructure. The education field is one of these advances. Through the numerous research initiatives being run, learning is being made more dependable and easy. E-learning is a technology that is advancing, and it won’t be long before it becomes popular and widely used. This is as a result of its many benefits over traditional physical education.